2020
DOI: 10.1371/journal.pone.0242870
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of undiagnosed hypertension among men in North Central Nigeria: Results from the Healthy Beginning Initiative

Abstract: Background The prevalence of hypertension in Nigeria is high and growing. The burden and risk factor distribution also vary by geographical zone. Information about prevalence, risk factors and disease status awareness are needed to guide evidence based public health response at the national and sub- national levels. Purpose This paper describes the prevalence of hypertension and its correlates, as well as hypertension status awareness among men in North Central, Nigeria. Methods A cross sectional survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 55 publications
1
19
2
1
Order By: Relevance
“…In the Peruvian population, a higher prevalence of hypertension has also been reported in men [ 35 , 36 ]. The higher probability of having undiagnosed hypertension in men could be explained by their lower awareness of hypertension as described in the literature [ 37 , 38 ]. In addition, it is reported that men have less adequate control of hypertension and blood pressure, which would explain the higher proportion of complications and death from cerebrovascular diseases in men, with hypertension leading among the main risk factors for death in the world.…”
Section: Discussionmentioning
confidence: 99%
“…In the Peruvian population, a higher prevalence of hypertension has also been reported in men [ 35 , 36 ]. The higher probability of having undiagnosed hypertension in men could be explained by their lower awareness of hypertension as described in the literature [ 37 , 38 ]. In addition, it is reported that men have less adequate control of hypertension and blood pressure, which would explain the higher proportion of complications and death from cerebrovascular diseases in men, with hypertension leading among the main risk factors for death in the world.…”
Section: Discussionmentioning
confidence: 99%
“…At least two visits were made for those study participants whose BP was elevated at the rst contact. According to the WHO guideline, a participant with systolic blood pressure (SBP) ≥140mmHg or diastolic blood pressure (DBP) ≥90mmHg will be diagnosed as a HTN case (19).…”
Section: Data Collectionmentioning
confidence: 99%
“…Undiagnosed HTN: adults (aged 18 years and above) will be considered undiagnosed for HTN if, at the time of the survey, he or she was diagnosed as hypertensive (SBP ≥140mmHg or DBP ≥90mmHg) but never took any prescribed antihypertensive medicine to lower or control blood pressure and was never been told by a health professional that they have HTN before this study (19).…”
Section: Operational De Nitionmentioning
confidence: 99%
“…With about 2277 health facilities18 providing comprehensive HIV treatment services across the 6 geopolitical regions of Nigeria, a total of 1.5 million people have been placed on ART 18. More recently, there have been efforts to build on the HIV service infrastructure by integrating testing for other diseases (e.g., hepatitis B, sickle cell disease, hypertension, perinatal depression)19–23 and integrating other health services (e.g., cancer prevention) 24…”
Section: Introductionmentioning
confidence: 99%